Feeding Treatment Based on Palm Oil Byproduct and Supplementation to Support Reproduction Performance of Bull - Ratnawati, Dian; Aryogi, Aryogi (ANIMAL PRODUCTION, 2016)
Palm oil waste (by product)can be used as a potential feed for livestock. Nevertheless, the study research of the effect of Palm oil waste (by product) as a feed to the bull performance was limited. The purpose of this research is to get technology to improve semen quality through improving protein ofÂ  feed based on palm oil waste (byproducts). This research was conducted in PTPN 6 Jambi andÂ  used 30 bulls that separated into 3 treatments, treatment I (feed protein 12% and suplementation), treatment II (feed protein 12%) and treatment III (existing feed, feed protein 10%). Parameter were measured i.e feed consumption, libido, sperm motility, mass movement, sperm concentration, sperm abnormality, volume, pH, consistency, colour, body condition score and average daily gain. Design of this research was completely randomized design. Data was analyzed use ANOVA. The result showed that there is no significantly different on semen quality between treatmens. Semen quality of three treatments were appropriate to standart of quality semen of bull (sperm abnormality <20%, sperm motility >50% and sperm concentration >500 million/ml). Based on this consideration, feed with protein level 10% more efficient because it needs less cost but results a good semen quality. The conclusion of this research is protein level 10% can supporting performance reproduction of bull.